Large-aperture polyurethane porous material as well as preparation method and application thereof
By using a high-pressure foaming machine and a specific raw material combination in the preparation of polyurethane porous materials, the problems of uneven pore size and large compression deformation rate of large pore size polyurethane porous materials are solved, and large pore size polyurethane porous materials with excellent performance are prepared, which is suitable for the production of ceramic filters.
Patent Information
- Application Number
- CN202510336056.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-21
AI Technical Summary
It is difficult to prepare large-porous polyurethane porous materials in the prior art, especially the problems of uneven pore size and large compression deformation rate, resulting in a decrease in product yield of ceramic filters.
Using specific synthetic polyurethane material raw materials and combining with the high-pressure foaming machine foaming process, large-porous polyurethane porous materials with uniform pore size are prepared by selecting suitable pore agents, catalysts and emulsifiers.
Large-pore polyurethane porous materials with pore sizes of 6-9 ppi were successfully prepared, with good tensile strength, elongation at break and tear strength, and low permanent compression deformation value, which is suitable for the production of large-pore ceramic filters.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material synthesis and processing, and in particular relates to a large-pore polyurethane porous material and a preparation method and application thereof. Background Art
[0002] Slag inclusion defect is a very important type of casting defect in the metal casting industry, accounting for more than half of the total defects. The control of slag inclusion defects is mainly based on the performance and purpose of the casting. The more precise and harsh the working conditions of the casting, the stricter the restriction on slag inclusion defects. How to reduce the proportion of slag inclusion has become an important issue faced by casting production. With the continuous development of casting technology, high-temperature filtration technology has gradually become an indispensable means to reduce slag inclusion in castings. By using foam ceramic filters with different pore sizes for graded filtration, slag, dross and other non-metallic inclusions can be effectively removed. There are currently several types of ceramic filters: alumina foam ceramic filter discs with a temperature resistance of 1200℃ can be used for copper-aluminum alloy filtration casting; silicon carbide foam ceramic filter discs with a temperature resistance of 1500℃ can be used for molten iron filtration casting; zirconia ceramic filter discs with a temperature resistance of 1700℃ can be used for molten steel filtration casting.
[0003] Large-pore polyurethane porous materials are mainly used in the production of large-pore ceramic filter template materials. Compared with polyether polyurethane materials, polyester polyurethane materials have higher bond energy and hydrogen bonding, so polyester sponge has higher tensile strength and tear strength. Therefore, polyester polyurethane porous materials are often selected as template materials for ceramic filters. The polyurethane porous material is impregnated with different ceramic slurries, then drained by rollers, and shaped and sintered to obtain ceramic filter sheets. At present, the preparation of large-pore polyurethane porous materials has the following problems: 1. The compression rebound deformation rate of the sponge is too large. Because in the roller pressing operation after the sponge is impregnated with ceramic slurry, the compression rebound deformation rate of the sponge is relatively large, and the size of the sponge after roller pressing is unstable, resulting in a decrease in the yield of ceramic filter products; 2. It is impossible to prepare coarse-pore polyurethane porous materials. For polyester sponges, the limit of the ppi value that can be achieved by the existing technology is more than 10, that is, the number of holes in the polyester sponge per unit inch cannot (or is difficult to) be less than 10; 3. The pore size distribution of polyurethane porous materials is uneven. After foaming, the pore size of the polyurethane porous material in the three-dimensional distribution of the foam block is quite different, resulting in a very low product yield.
[0004] The above difficulties in the preparation of large-pore polyurethane porous materials are mainly due to the following reasons: 1. Large-pore polyurethane porous materials are supported by a three-dimensional network skeleton structure. If the molecular structure is not sufficiently cross-linked during the polyurethane foaming process, the compression resilience of the network material will decrease; 2. During the foaming process of the sponge, the foaming reaction and the gel reaction are carried out simultaneously, and the matching of the two is crucial. The larger the pore size of the material, the greater the grid gap during the process of forming to the limit sponge pore size, and the lower the strength of the skeleton connector connecting the grids. After the sponge is foamed, if a conventional foaming system is used alone, the gel speed will be slow. Unable to keep up with the foaming rate, the skeleton strength is insufficient to support the entire foam, that is, the foam will collapse, and a large-pore sponge cannot be formed; 3. Since the primary hydroxyl-terminated polyester polyol has a strong reactivity, if a strong gel catalyst or a highly reactive MDI is added during the foaming process, it is easy to cause excessive post-ripening gelation, and the sponge will shrink after aging, and a large-pore sponge cannot be formed; 4. During the foaming process, due to the effect of the sponge's own gravity, as well as the influence of the edge film and bottom paper, it is easy to cause the material to have a large difference in the three-dimensional distribution of the pore size in the foam block after foaming, resulting in a decrease in the yield of qualified products.
[0005] The invention patent with application number 201310182491.1 discloses a method for preparing a large-pore polyurethane mesh material by using a mixed polyol composed of polyether polyol, polymer polyether polyol and polyester polyol and foaming with toluene diisocyanate, and applying the method to prepare foam ceramics. However, the method can only prepare a polyurethane mesh material with a pore size of more than 10ppi, and cannot prepare a large-pore polyurethane porous material with a pore size of less than 10ppi. In addition, polyester polyol is terminated with primary hydroxyl groups, while polyether polyol is terminated with secondary hydroxyl groups. The reaction activities of the two with isocyanate are quite different. Direct foaming will cause the bubbles to form disordered pores, and a polyurethane porous material with uniform pore size cannot be obtained. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the present invention provides a large-pore polyurethane porous material and a preparation method and application thereof. The present invention selects specific raw materials for synthesizing polyurethane materials, as well as the selection of pore-opening agents, catalysts, and emulsifiers, which can be well applied to the foaming process of a high-pressure foaming machine, and solves the problems of difficulty in foaming large-pore polyurethane porous materials and large material compression deformation rate. More importantly, a large-pore polyurethane porous material with uniform pore size can be prepared to meet the production material requirements of large-pore ceramic filters.
[0007] The technical solution provided by the present invention is as follows:
[0008] A method for preparing a large-pore polyurethane porous material, comprising the following raw materials, measured by weight: 35-50 parts of toluene diisocyanate, 5-15 parts of polymethylene polyphenyl polyisocyanate raw materials, 80-120 parts of polyester polyol, 2-6 parts of chain extender, 0.5-2 parts of catalyst, 0.5-2 parts of foam stabilizer, 1-4 parts of emulsifier, 2-6 parts of pore opener, and 3-5 parts of water;
[0009] It includes the following steps:
[0010] 1) First, store the polyester polyol in a constant temperature storage tank, decompress and dehydrate it after heating, and then cool it to obtain component A;
[0011] 2) Evenly mix water, chain extender, catalyst, foam stabilizer, emulsifier and cell opener to obtain composite component B;
[0012] 3) Component A, component B, toluene diisocyanate, and polymethylene polyphenyl polyisocyanate are placed in different storage tanks in a high-pressure foaming machine, and the temperature is kept constant at 25°C. According to the raw material ratio, the raw material components are injected into the mixing head of the high-pressure foaming machine at a pressure of 20-50 bar. The mixing speed of the mixing head is 4000-6000 r / min, and the pressure of the mixing head is 1-2 bar. After the materials are mixed and reacted in the mixing head, they are injected into the foaming box and aged in an oven;
[0013] 4) The obtained blocky polyurethane foam is subjected to explosion treatment to obtain a full-skeleton open-cell foam, which is then cut to obtain a large-pore polyurethane porous material with a pore size of 6-9 ppi.
[0014] In the foaming of large-pore polyurethane porous materials, the larger the pore size of the sponge, the larger the grid gaps during its molding process, resulting in a large amount of collapse before enough gel enters the sponge after foaming, and the strength of the connector skeleton connecting the grids is insufficient, making it impossible to form a large-pore sponge.
[0015] Since the two NCO groups in the structure of diphenylmethane diisocyanate (MDI) are far apart and there are no substituents around, the steric hindrance of the NCO groups is low, while the two NCO groups in TDI are on the same benzene ring and have methyl substituents, which have a certain steric hindrance effect. Therefore, the reaction activity of the NCO groups in MDI is relatively high, and polymethylene polyphenyl polyisocyanates can quickly form a gel reaction. At the same time, the multifunctional isocyanate in MDI can play a cross-linking branching role, quickly enhance the strength of the grid connector skeleton, and solve the problem of collapse. At the same time, more branching cross-linking in the molecular structure provides better compression rebound performance for the material. This is exactly what the present invention needs for isocyanates using an efficient high-pressure foaming process, and it is also the reason why the present invention, in addition to using toluene diisocyanate, further adds polymethylene polyphenyl polyisocyanate raw materials.
[0016] Specifically: the toluene diisocyanate is a mixture of TDI80 and TDI65, and the weight ratio of TDI80 to TDI65 is 1:2 to 1:3.
[0017] Specifically, the polymethylene polyphenyl polyisocyanate raw material is crude MDI, wherein the molar amount of MDI accounts for 50%, and the molar amount of polyisocyanate with a functionality greater than 2 accounts for 50%.
[0018] Specifically, the general formula of the pore opening agent is as follows:
[0019]
[0020] in:
[0021] 40≤x≤80, 30≤y≤60, x / y=0.5 to 0.8;
[0022] The number average molecular weight is 2000-4000 g / mol.
[0023] The above-mentioned cell opening agent is a block copolymer of polyoxyethylene and polyoxypropylene with ethylene glycol as an initiator, with a number average molecular weight of 2000-4000 g / mol, wherein the content of polyoxyethylene is 50-80%.
[0024] In the TDI / MDI combined isocyanate foaming system, due to the high reactivity of the terminal primary hydroxyl group of polyester polyol and the high activity of the isocyanate group in MDI, the prepared polyurethane foam material has a high closed cell rate, and the material tends to shrink during the post-ripening process. The polyoxyethylene and polyoxypropylene block copolymer cell opener with ethylene glycol as the initiator is a low-foaming non-ionic surfactant. In the middle and late stages of the polyurethane foaming stage, as the reaction releases heat and the system temperature rises, the cell growth gradually tends to be stable. The cell opener can effectively increase the surface tension of the foam film, making it easier for the gas to break through each cell, promoting the penetration between the cells, and ensuring that the material does not shrink during the post-ripening process.
[0025] Specifically, the polyester polyol is obtained by esterification and polycondensation of adipic acid and diethylene glycol using trimethylolpropane as an initiator, and has a functionality of 2.5-3 and a hydroxyl value of 55-65 mg KOH / g.
[0026] Specifically, the catalyst is selected from any one or more of 1,4-dimethylpiperazine, N-methylmorpholine, 2,2-dimorpholinyl diethyl ether or bis(dimethylaminoethyl) ether.
[0027] Specifically, the general formula of the polycarbonate diol chain extender is as follows:
[0028]
[0029] Where 3≤m≤5;
[0030] R 1 The corresponding monomer alcohol is 1,5-pentanediol or 1,6-ethylene glycol;
[0031] The hydroxyl value is 200-300 mg KOH / g.
[0032] The polycarbonate groups mentioned above have high thermal stability and bond energy. By using short molecular chain polycarbonate diol as a chain extender and inserting the carbonate groups into the polyurethane molecular chain, the strength and compression resilience of the material can be improved.
[0033] Specifically, the foam stabilizer is selected from any one of TEGOSTAB B8301, TEGOSTAB B8335 or VORASURFDC1990 or a mixture of several thereof.
[0034] Specifically, the general formula of the emulsifier is as follows:
[0035]
[0036] Among them, 7≤n≤21, R 2 The corresponding monomer is a saturated alkyl group of dodecanoic acid, dodecanoic acid or tetradecanoic acid.
[0037] For example, it is polyethylene glycol di-saturated fatty acid ester, or polyethylene glycol di-fatty acid ester in which the degree of polymerization of polyethylene glycol is 7-21, or the saturated fatty acid is one of dodecanoic acid, dodecanoic acid and tetradecanoic acid.
[0038] As a nonionic emulsifier, the ester structure in the molecule of polyethylene glycol disaturated fatty acid ester has good compatibility with polyester polyurethane materials. The hydrophilic EO group and the lipophilic alkyl group in its structural unit constitute a water-in-oil (W / O) emulsification system, which can emulsify, disperse and thicken the mixed reaction liquid in the early stage of the foaming reaction, thereby improving the stability of the cell size after foaming.
[0039] The method for preparing the macroporous polyurethane material may specifically include the following steps:
[0040] 1) First, store the polyester polyol in a constant temperature storage tank, raise the temperature to 80-100°C, decompress and dehydrate to remove bubbles at a negative pressure of -0.05 to -0.09 MPa for 2-5 hours, and then cool to 20-25°C to obtain component A;
[0041] 2) Evenly mix water, chain extender, catalyst, foam stabilizer, emulsifier and cell opener to obtain composite component B;
[0042] 3) Component A, component B, toluene diisocyanate, and polymethylene polyphenyl polyisocyanate are placed in different storage tanks in a high-pressure foaming machine, and the temperature is kept constant at 25°C. According to the raw material ratio, the raw material components are injected into the mixing head of the high-pressure foaming machine at a pressure of 20-50 bar. The mixing speed of the mixing head is 4000-6000 r / min, and the pressure of the mixing head is 1-2 bar. After the materials are mixed and reacted in the mixing head, they are injected into the foaming box and aged in an oven at 60°C for 24 hours;
[0043] 4) The obtained blocky polyurethane foam is subjected to blasting treatment to obtain a full-frame open-cell foam, and after cutting off the edge material, it is cut into required sizes to obtain a large-pore polyurethane porous material.
[0044] Since bubbles will be introduced into the raw materials during transportation and storage, especially polyester polyols with higher viscosity, the bubbles entrapped in the polyester polyols are difficult to be discharged automatically. If the polyester polyols are not pre-treated to remove bubbles, these bubbles will form tiny bubble nucleation points in the mixing head at the initial stage of foaming, which will play a role in refining the pores, making it difficult to prepare large-pore polyurethane porous materials.
[0045] The present invention also provides a large-pore polyurethane porous material prepared by the above preparation method, with a pore size of 6-9ppi, good pore size distribution uniformity, good tensile strength, elongation at break and tear strength, and a very low permanent compression deformation value.
[0046] The present invention also provides an application of the above-mentioned large-pore polyurethane porous material, and a large-pore ceramic filter is obtained by impregnating the large-pore polyurethane porous material with ceramic slurry, rolling and draining, and then sintering at high temperature.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1) The present invention uses toluene diisocyanate and polymethylene polyphenyl polyisocyanate to form a combined isocyanate, and utilizes the rapid gelation reaction and branching cross-linking effect of polymethylene polyphenyl polyisocyanate to solve the problem of easy collapse of large-pore polyurethane porous materials during foaming, while improving the compression rebound performance of the material and the dimensional stability of the large-pore polyurethane porous material during the sizing roller pressing operation in the ceramic filter production process.
[0049] 2) The present invention performs a pretreatment of heating and reducing pressure to remove bubbles on polyester polyols with high viscosity, which effectively removes bubbles entrapped in the raw materials and the original nucleation points in the foaming process, creating favorable conditions for the preparation of large-pore polyurethane porous materials.
[0050] 3) The present invention innovatively uses short molecular chain polycarbonate diol as a chain extender, and utilizes the higher thermal stability and bond energy of the polycarbonate group to effectively improve the strength and compression rebound performance of the material.
[0051] 4) The present invention uses a polyethylene glycol disaturated fatty acid ester type water-in-oil (W / O) emulsifier that has good compatibility with polyester polyurethane materials to emulsify, disperse and thicken the mixed reaction liquid at the initial stage of the foaming reaction, thereby improving the stability of the pore size and solving the problem of unstable pore size of large-pore polyurethane porous materials.
[0052] 5) The present invention effectively solves the problem of closed-cell shrinkage of the TDI / MDI combined isocyanate system during the foaming process of the polyester polyurethane foam material by using a cell-opening agent of polyoxyethylene and polyoxypropylene block copolymers with ethylene glycol as an initiator. DETAILED DESCRIPTION
[0053] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0054] Unless otherwise specified, the test methods used in the examples are conventional methods; the materials and reagents used are commercially available reagents and materials unless otherwise specified.
[0055] The specific brands of raw materials used in the embodiments are described in detail below: toluene diisocyanate is WANNATE® TDI-80 and WANNATE® TDI-65 from Wanhua Chemical; polymethylene polyphenyl polyisocyanate is Lupranate M20S from BASF; polyester polyol is PF601 from Stepan (Nanjing) Chemical Co., Ltd., with a hydroxyl value of 60 mg KOH / g; foam stabilizers are TEGOSTAB B8301 and TEGOSTAB B8335 from Evonik Chemical and VORASURF DC1990 from Dow Chemical; polycarbonate diol chain extender is ETERNACOLL PH-50 from Ube Chemicals of Japan, with a hydroxyl value of 224 mg KOH / g; emulsifier is PEG400DL from Hai'an Petrochemical Plant of Jiangsu Province, and its specific component is polyethylene glycol 400 dilaurate; and cell opener is Pluronic PE6200 from BASF.
[0056] Examples 1-5
[0057] The method for preparing a large-pore polyurethane porous material provided in Examples 1-5 comprises the following process steps:
[0058] (1) The polyester polyol PF601 in Example 1-5 was stored in a constant temperature storage tank, heated to 90° C., decompressed and dehydrated to remove bubbles for 3 hours at a negative pressure of -0.08 MPa, and then cooled to 25° C. to obtain a pretreated polyester polyol component A;
[0059] (2) The water, chain extender ETERNACOLL PH-50, catalyst, foam stabilizer, emulsifier PEG400DL, and cell opener Pluronic PE6200 in Examples 1-5 are mixed uniformly to obtain a composite component B;
[0060] (3) Component A and component B in Examples 1-5, as well as WANNATE® TDI-80, WANNATE® TDI-65, and Lupranate M20S were placed in different storage tanks in a high-pressure foaming machine, respectively, and the temperature was kept constant at 25°C. According to the raw material ratio, the raw material components were injected into the mixing head of the high-pressure foaming machine at a pressure of 40 bar. The stirring speed of the mixing head was 5000 r / min, and the pressure of the mixing head was 1.5 bar. After the materials were mixed and reacted in the mixing head, they were injected into the foaming box and aged in an oven at 60°C for 24 hours;
[0061] (4) The obtained blocky polyurethane foam is subjected to blasting treatment to obtain a full-frame open-cell foam. After the edge material is cut off, it is cut into required sizes to obtain a large-pore polyurethane porous material.
[0062] Comparative Examples 1-5
[0063] Comparative Example 1 is based on Example 1, in which Lupranate M20S is replaced by T80 and T65, that is, T80 and T65 are used for all isocyanates.
[0064] The preparation method of Comparative Example 1 comprises the following process steps:
[0065] (1) The polyester polyol PF601 in Comparative Example 1 was stored in a constant temperature storage tank, heated to 90° C., decompressed and dehydrated to remove bubbles for 3 hours at a negative pressure of -0.08 MPa, and then cooled to 25° C. to obtain a pretreated polyester polyol component A;
[0066] (2) The water, chain extender ETERNACOLL PH-50, catalyst, foam stabilizer, emulsifier PEG400DL, and cell opener Pluronic PE6200 in Comparative Example 1 were mixed uniformly to obtain a composite component B;
[0067] (3) Component A and component B obtained in the above steps, as well as WANNATE® TDI-80 and WANNATE® TDI-65, were placed in different storage tanks in a high-pressure foaming machine, and the temperature was kept constant at 25°C. According to the raw material ratio, the raw material components were injected into the mixing head of the high-pressure foaming machine at a pressure of 40 bar. The stirring speed of the mixing head was 5000 r / min, and the pressure of the mixing head was 1.5 bar. After the materials were mixed and reacted in the mixing head, they were injected into the foaming box and aged in an oven at 60°C for 24 hours.
[0068] Comparative Example 2 is based on Example 2 except that the chain extender ETERNACOLL PH-50 is removed.
[0069] The preparation method of Comparative Example 2 comprises the following process steps:
[0070] (1) The polyester polyol PF601 in Comparative Example 2 was stored in a constant temperature storage tank, heated to 90° C., decompressed and dehydrated to remove bubbles for 3 hours at a negative pressure of -0.08 MPa, and then cooled to 25° C. to obtain a pretreated polyester polyol component A;
[0071] (2) The water, catalyst, foam stabilizer, emulsifier PEG400DL and pore opening agent PluronicPE6200 of Comparative Example 2 were mixed uniformly to obtain a composite component B;
[0072] (3) Component A and component B obtained in the above steps, as well as WANNATE® TDI-80, WANNATE® TDI-65, and Lupranate M20S were placed in different storage tanks in a high-pressure foaming machine, and the temperature was kept constant at 25°C. According to the raw material ratio, the raw material components were injected into the mixing head of the high-pressure foaming machine at a pressure of 40 bar. The stirring speed of the mixing head was 5000 r / min, and the pressure of the mixing head was 1.5 bar. After the materials were mixed and reacted in the mixing head, they were injected into the foaming box and aged in an oven at 60°C for 24 hours;
[0073] (4) The obtained block polyurethane foam is subjected to blasting treatment to obtain a full-frame open-cell foam. After cutting off the edge material, it is cut into pieces according to the required size.
[0074] Comparative Example 3 is based on Example 3 except that the emulsifier PEG400DL is removed.
[0075] The preparation method of Comparative Example 3 comprises the following process steps:
[0076] (1) The polyester polyol PF601 in Example 1-5 was stored in a constant temperature storage tank, heated to 90° C., decompressed and dehydrated to remove bubbles for 3 hours at a negative pressure of -0.08 MPa, and then cooled to 25° C. to obtain a pretreated polyester polyol component A;
[0077] (2) The water, chain extender ETERNACOLL PH-50, catalyst, foam stabilizer, and cell opener Pluronic PE6200 in Examples 1-5 are uniformly mixed to obtain a composite component B;
[0078] (3) Component A and component B obtained in the above steps, as well as WANNATE® TDI-80, WANNATE® TDI-65, and Lupranate M20S were placed in different storage tanks in a high-pressure foaming machine, and the temperature was kept constant at 25°C. According to the raw material ratio, the raw material components were injected into the mixing head of the high-pressure foaming machine at a pressure of 40 bar. The stirring speed of the mixing head was 5000 r / min, and the pressure of the mixing head was 1.5 bar. After the materials were mixed and reacted in the mixing head, they were injected into the foaming box and aged in an oven at 60°C for 24 hours;
[0079] (4) The obtained block polyurethane foam is subjected to blasting treatment to obtain a full-frame open-cell foam. After cutting off the edge material, it is cut into pieces according to the required size.
[0080] Comparative Example 4 is based on Example 4, except that the pore opening agent Pluronic PE6200 is removed.
[0081] The preparation method of Comparative Example 4 comprises the following process steps:
[0082] (1) The polyester polyol PF601 in Comparative Example 4 was stored in a constant temperature storage tank, heated to 90° C., decompressed and dehydrated to remove bubbles for 3 hours at a negative pressure of -0.08 MPa, and then cooled to 25° C. to obtain a pretreated polyester polyol component A;
[0083] (2) The water, chain extender ETERNACOLL PH-50, catalyst, foam stabilizer and emulsifier PEG400DL in Comparative Example 4 were mixed uniformly to obtain a composite component B;
[0084] (3) Component A and component B obtained in the above steps, as well as WANNATE® TDI-80, WANNATE® TDI-65, and Lupranate M20S were placed in different storage tanks in a high-pressure foaming machine, and the temperature was kept constant at 25°C. According to the raw material ratio, the raw material components were injected into the mixing head of the high-pressure foaming machine at a pressure of 40 bar. The stirring speed of the mixing head was 5000 r / min, and the pressure of the mixing head was 1.5 bar. After the materials were mixed and reacted in the mixing head, they were injected into the foaming box and aged in an oven at 60°C for 24 hours.
[0085] Comparative Example 5 is based on Example 5, but the polyester polyol is directly foamed without being subjected to a pretreatment of heating and degassing.
[0086] The preparation method of Comparative Example 5 comprises the following process steps:
[0087] (1) The water, chain extender ETERNACOLL PH-50, catalyst, foam stabilizer and emulsifier PEG400DL in Comparative Example 5 were mixed uniformly to obtain a composite component A;
[0088] (2) Place polyester polyol PF601, component A, WANNATE® TDI-80, WANNATE® TDI-65, and Lupranate M20S in different storage tanks in a high-pressure foaming machine, keep the temperature constant at 25°C, and inject the raw material components into the mixing head of the high-pressure foaming machine at a pressure of 40 bar according to the raw material ratio. The mixing speed of the mixing head is 5000 r / min, and the pressure of the mixing head is 1.5 bar. After the materials are mixed and reacted in the mixing head, they are injected into the foaming box and aged in an oven at 60°C for 24 hours.
[0089] (3) The obtained block polyurethane foam is subjected to blasting treatment to obtain a full-frame open-cell foam. After cutting off the edge material, it is cut into pieces according to the required size.
[0090] Table 1 shows the raw material composition and the number of parts of the examples and comparative examples:
[0091]
[0092] The foaming results and test results of Examples 1-5 and Comparative Examples 1-5 are shown in Table 2.
[0093] Table 2 is the test results of the physical properties of the examples and comparative examples
[0094]
[0095] Note: Aperture standard deviation , where N is the total number of sampled test cells,
[0096] d i is the pore size of any pore (in mm), d is the average pore size of sampled pores (in mm), and the sampling positions of the sampled test pores are fixed and distributed in the upper, middle and lower layers of the foam body and in different axial directions of each layer.
[0097] It can be seen from the test results of the above embodiments and comparative examples that the large-pore polyurethane porous materials prepared in Examples 1-5 have high strength, low compression deformation rate, good pore size distribution uniformity, and pore sizes all reach below 10ppi, and can be used as template materials for preparing large-pore ceramic filters; Comparative Example 1 lacks polymethylene polyphenyl polyisocyanate, and cannot quickly gel to form a skeleton structure of sufficient strength during the foaming process, collapses during the foaming process, and cannot obtain a normal polyurethane foam material; Comparative Example 2 does not have a polycarbonate group unit inserted into the polyurethane molecular chain, so the strength and permanent compression deformation of the material are large, and it cannot meet the production requirements of large-pore ceramic filters; Comparative Example 3 lacks an emulsifier, and after the polyurethane is foamed, the pore size has a large deviation in the three-dimensional distribution of the foam, resulting in only some dimensions of the foam meeting the requirements, and the final material yield is low; Comparative Example 4 lacks a pore opening agent Pluronic PE6200 can foam normally to the top during the foaming process, but due to the serious closed-cell nature of the cell units, the foam shrinks during the post-ripening process, and a normal polyurethane foam material cannot be obtained; in Comparative Example 5, since the high-viscosity polyester polyol was not subjected to a temperature-raising degassing treatment before foaming, the bubbles entrapped in the polyester polyol played a nucleation role during foaming, refined the cells, and made it impossible to prepare a large-pore polyurethane porous material below 10ppi.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a large-pore polyurethane porous material, characterized in that: The raw materials include the following in parts by mass: 35-50 parts of toluene diisocyanate, 5-15 parts of polymethylene polyphenyl polyisocyanate raw materials, 80-120 parts of polyester polyol, 2-6 parts of chain extender, 0.5-2 parts of catalyst, 0.5-2 parts of foam stabilizer, 1-4 parts of emulsifier, 2-6 parts of cell opener, and 3-5 parts of water; It includes the following steps: 1) First, store the polyester polyol in a constant temperature storage tank, decompress and dehydrate it after heating, and then cool it to obtain component A; 2) Evenly mix water, chain extender, catalyst, foam stabilizer, emulsifier and cell opener to obtain composite component B; 3) Component A, component B, toluene diisocyanate, and polymethylene polyphenyl polyisocyanate are placed in different storage tanks in a high-pressure foaming machine, and the temperature is kept constant at 25°C. According to the raw material ratio, the raw material components are injected into the mixing head of the high-pressure foaming machine at a pressure of 20-50 bar. The mixing speed of the mixing head is 4000-6000 r / min, and the pressure of the mixing head is 1-2 bar. After the materials are mixed and reacted in the mixing head, they are injected into the foaming box and aged in an oven; 4) The obtained blocky polyurethane foam is subjected to explosion treatment to obtain a full-skeleton open-cell foam, which is then cut to obtain a large-pore polyurethane porous material with a pore size of 6-9 ppi.
2. The method for preparing a large-pore polyurethane porous material according to claim 1, characterized in that: The toluene diisocyanate is a mixture of TDI80 and TDI65, and the mass ratio of TDI80 to TDI65 is 1:2 to 1:
3.
3. The method for preparing a large-pore polyurethane porous material according to claim 1, characterized in that: The general formula of the pore opening agent is as follows: in: 40≤x≤80, 30≤y≤60, x / y=0.5 to 0.8; The number average molecular weight is 2000-4000 g / mol.
4. The method for preparing a large-pore polyurethane porous material according to claim 1, characterized in that: The polymethylene polyphenyl polyisocyanate raw material is crude MDI, wherein the molar amount of MDI accounts for 50%, and the molar amount of polyisocyanate with a functionality greater than 2 accounts for 50%.
5. The method for preparing a macroporous polyurethane material according to claim 1, characterized in that: The polyester polyol is obtained by esterification and polycondensation of adipic acid and diethylene glycol using trimethylolpropane as an initiator, and has a functionality of 2.5-3 and a hydroxyl value of 55-65 mg KOH / g.
6. The method for preparing a large-pore polyurethane porous material according to claim 1, characterized in that: The catalyst is selected from any one or more of 1,4-dimethylpiperazine, N-methylmorpholine, N-ethylmorpholine, 2,2-dimorpholinyl diethyl ether or bis(dimethylaminoethyl) ether.
7. The method for preparing a macroporous polyurethane material according to claim 1, characterized in that: The chain extender is a polycarbonate diol with a high hydroxyl value, and its general formula is as follows: in: 3≤m≤5; The monomer alcohol corresponding to R1 is 1,5-pentanediol or 1,6-ethylene glycol; The hydroxyl value is 200-300 mg KOH / g.
8. The method for preparing a large-pore polyurethane porous material according to claim 1, characterized in that: The foam stabilizer is selected from any one of TEGOSTAB B8301, TEGOSTAB B8335 or VORASURF DC1990 or a mixture of several thereof; And / or, the general formula of the emulsifier is as follows: Wherein, 7≤n≤21, and the monomer corresponding to R2 is a saturated alkyl group of dodecanoic acid, dodecanoic acid or tetradecanoic acid.
9. A large-pore polyurethane porous material prepared according to the preparation method according to any one of claims 1 to 8.
10. An application of the large-pore polyurethane porous material according to claim 9, characterized in that: The large-pore ceramic filter is obtained by impregnating the large-pore polyurethane porous material with ceramic slurry, rolling and draining it, and then sintering it at high temperature.
Citation Information
Patent Citations
Method for preparing high-density large-aperture polyurethane mesh material
CN103275299A
Polyester type ultra-low density polyurethane resin for shoes
CN101148493A
High oil absorption polyurethane foam and preparation method thereof
CN101987884A
Self-repairing coating composition, self-repairing coating layer, protective film containing coating layer and application of protective film
CN108239446A
Polyester type large-aperture filtration sponge for ceramic filter and preparation method of large-aperture filtration sponge
CN109384901A